Tailoring nanoparticles for targeted drug delivery: From organ to subcellular level. Issue 5 (4th May 2021) - Liang, Tingxizi; Xing, Zejing; Jiang, Liping; Zhu, Jun‐Jie
Abstract: An effective dose at specific sites is of paramount importance for disease therapy. While therapeutic reagents such as small molecule drugs, nucleic acids, peptides, and proteins are suffered from degradation or clearance by physiological environment, nanomedicine has emerged to improve drug delivery efficiency due to their superior targeting ability. By tailoring the properties of nanoparticle, including size, shape, surface chemistry, site‐specific drug delivery in organ, cellular, and subcellular level could be achieved. This minireview highlights recent advances in the development of targeted drug delivery system for disease therapy. Abstract : Targeted drug delivery systems have promising applications in disease therapy. The authors herein have reviewed recent advances of targeted drug delivery systems based on engineered nanoparticles. The tailorable properties of nanoparticles, including size, shape, and surface chemistry, could be manipulated to achieve effective targeting from organ to subcellular level.